School management in the development of promoting democratic management - Morais, Andeson Carlos Santos (Seven Editora, 2023)
This scientific article investigates the relevance of School Management through: school management and pedagogical coordination in the context of the promotion of democratic management in educational institutions. Democratic management is an essential approach to establishing inclusive and effective educational environments, as well as being fundamental to promoting the active participation of all those involved in the educational process. In this article, we explore the role of these professionals in facilitating democratic management, identifying their responsibilities, challenges, and strategies to promote democratic participation in the school environment. We discuss how these professionals can positively influence decision-making, communication, and the construction of an inclusive and participatory school environment. In addition, we provide citations and references from academic studies to support our arguments. DOI:https://doi.org/10.56238/sevened2023.006-067